Madrasah curriculum development - Rovi'i, Abdul; Ahid, Nur; Arif Musafak, Muhammad; Kurniadi, Yanwar (Educenter : Jurnal Ilmiah Pendidikan, 2023)
The development of madrasah curriculum in Indonesia has undergone various transformations since the colonial period until now. The purpose of this research is to find out the development of madrasah curriculum in Indonesia. The research method used by researchers is library research. Based on the analysis, it can be concluded that the development of madrasah curriculum in Indonesia has undergone significant changes, especially after Indonesia's independence. The Indonesian government issued various policies to advance education in Indonesia, including Islamic religious education and madrasah. One of the policies issued is the integration between the general education curriculum and Islamic religious education in madrasas. The government can provide adequate financial support and experts for madrasah curriculum development. The community can support through active participation in educational activities, such as providing educational facilities and infrastructure. The industrial world can provide support in the form of internship programs and cooperation with madrasah to improve student skills. In the development of madrasah curriculum in Indonesia, there have been significant changes and developments since the establishment of Madrasah Aliyah in 1945. The currently implemented madrasah curriculum, the 2013 curriculum, has integrated general and religious education in a more balanced manner.